Fluid resuscitation of at least 30 mL/kg was not associated with decreased mortality in patients with infection, signs of hypoperfusion, and a do‐not‐intubate order. Issue 1 (30th September 2022) - Matsuda, Wataru; Funato, Yumi; Miyazaki, Momoyo; Tomiyama, Koichiro
Abstract : Aim: Administration of at least 30 mL/kg of fluid as fluid resuscitation is recommended for patients with sepsis and signs of hypoperfusion. However, it is not clear whether this is appropriate for patients with a do‐not‐intubate (DNI) order. This study evaluated the association between volume of fluid resuscitation and outcomes in patients with infection, signs of hypoperfusion, and a DNI order in an emergency department. Methods: This was a single‐center retrospective cohort study. We classified the infected patients with signs of hypoperfusion and a DNI order seen in our emergency department between April 1, 2015 and November 31, 2020 into the standard fluid resuscitation group (≥30 mL/kg) and the restricted fluid resuscitation group (<30 mL/kg). We compared with in‐hospital mortality and the rate of discharge to home in two groups. Results: Of 367 patients, 149 received standard fluid resuscitation and 218 received restricted fluid resuscitation. In‐hospital mortality was similar in each group (40/149 and 62/218, respectively). Standard fluid resuscitation was not associated with in‐hospital mortality (adjusted odds ratio [aOR], 1.05; 95% confidence interval [CI], 0.62–1.77, P  = 0.86), but was associated with a significantly lower rate of discharge to home (aOR, 0.55; 95% CI, 0.30–0.98, P  = 0.043). There was no significant difference in respiratory rate or need for oxygen therapy post‐resuscitation between the two groups. Conclusion: This study suggests that fluid resuscitation may be not beneficial for infected patients with signs of hypoperfusion and a DNI order. Further studies should be conducted on the options for resuscitation management for these patients. Abstract : In patients with infection, signs of hypoperfusion and a DNI order, at least 30 mL/kg of fluid as resuscitation was not associated with in‐hospital mortality but was associated with a significantly lower rate of discharge to home.